Social Credit The Warring States of China's Emerging Data Empire - Brussee, Vincent (Singapore : Springer Nature Singapore : Imprint: Palgrave Macmillan, 2023)
"Vincent Brussee is one of the very few scholars who I regularly recommend as essential reading on China's social credit system. For years, he has remained consistently abreast of the latest developments in this complicated and evolving area, and his writing has helped to dispel the fog of misinformation that surrounds the subject in popular media." --Jeremy Daum, Senior Research Fellow, Paul Tsai China Center, Yale University School of Law "China's Social Credit System has been a source for fanciful speculation and gratuitous mythmaking. How does it actually work in practice? This book provides a rigorous and detailed review of the system's historical evolution, its structuring, and its functionality and dysfunctionality. It provides a useful corrective to dominant narratives, as well as a fascinating insight into governance reform in China." - Rogier Creemers, Assistant Professor at Leiden University China's Social Credit System has fundamentally re-shaped global notions of surveillance, making it into European Union legislation and hundreds of media headlines. Drawing on a rich body of empirical evidence, this book offers one of the first comprehensive assessments of this infamous system, from its fragmented implementation to its implications for both human rights and the market order. Surprisingly, it illustrates even China's government is confused about this messy initiative. Separating fact from fiction, Social Credit is an invaluable resource for anyone interested in technology, governance, and surveillance in China and beyond. Vincent Brussee is an Analyst at the Mercator Institute for China Studies, Europe's largest think tank and research institute on contemporary China. He is the institute's lead researcher on the Social Credit System. In addition to publishing extensively for MERICS, his work has been featured in Foreign Policy, the Diplomat, and various national outlets in Europe. He holds a graduate degree with the highest distinction in Asian Studies from Leiden University (the Netherlands), focusing on China's domestic governance.
Chapter 1. Introduction -- Chapter 2. The Social Credit System's emergence and global roots -- Chapter 3. The Policy Umbrella of Social Credit -- Chapter 4. Limitless Expansion, Fragmented Development: A Policy History of the Social Credit System (2002-2020) -- Chapter 5: No Credit for Culprits -- Chapter 6. One Step Back to Put More Forward: The Covid-19 Pandemic and Its Aftermath -- Chapter 7. Mythbusters: anatomy of social credit scoring -- Chapter 8. The future of the Social Credit System.
Keywords: Asia -- Politics and government; Crime; Technology; Crime -- Sociological aspects; Asian Politics; Crime and Technology; Crime and Society